Legal Regulation of Spreading Opinions and Beliefs through TV Broadcasting - S. A. Kucher (Law and Safety)
The research is focused on the problems of legal regulation of spreading opinions and beliefs through TV broadcasting. The scientific novelty of the research consists of the provisions on the need to amend the legislation on establishing the procedure for inspection and monitoring of television organizations by the National Council on Television and Radio Broadcasting. The author has studied legislative acts regulating the activity of mass media and works of scholars, where the peculiarities of the legal status of television organizations are covered.